INTELEKTUALISME SANTRI DALAM SISTEM POLITIK ORDE BARU - Mulkhan, Abdul munir (Jurnal Bestari, 1992)
Muslims consitute the gretest number in Indonesia. They have struggled to establish Indonesia since years ago, The proclamation of its liberaty cannot be separated from their contribution. The develpoment program which has started since then includes political affairs. As the greatest part. Muslimss give an important role develop the system of indonesian politics. Thier contribution to develop political affairs especially is shown by muslim intellectuals in many political instituions.